Catch composition of deep-sea resources of commercial importance in the Colombian Caribbean - Grijalba-Bendeck, Marcela; Paramo, Jorge; Wolff, Matthias (Revista de Biología Marina y Oceanografía, 2019)
Recent studies in the Colombian Caribbean Sea describe the potential for a new deep-sea crustacean fishery between 200 a 550-m depth. In order to support appropriate management plans for their sustainable utilization, the goal of the present study was to identify the catch composition and to detect general trends in the bathymetric distribution of the main four biological categories (crustaceans, teleostean, chondrichthyes and molluscs), in relation to depth strata. A total catch per unit area of 8,759 ind. km-2 and 226 kg km-2 was reported and the major contribution was supported by teleostean fish (89 species; 62% abundance and 73% of total biomass), dominating the depth stratum 200-300 m, followed by crustaceans (36% and 22%, respectively) for deeper waters (> 500 m). Most important species were the fish Coelorinchus caelorhincus (20.2 ind. km-2; 16.7 kg km-2) and the crustaceans Penaeopsis serrata (579 ind. km-2, 7% of the total abundance) and Pleoticus robustus (12.6 kg km-2, 6% of the total biomass). The information obtained is part of a base line required to describing the potential effects of deep-sea fisheries on the ecosystem and supporting future decisions about use, management and conservation of deep resources for this region.